ANALISIS KINERJA UMKM DARI PERSPEKTIF PRODUKSI DAN KEUANGAN PADA UMKM PATUNG UANG KEPENG DI MAS UBUD - Juniariani, Ni Made Rai; Mariyatni, Ni Putu Sri; Widhiastuti, Ni Luh Putu; Sunata, I Gede Ngurah (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2019)
Bali has been known as an area of ??art with a variety of cultural characteristics and customs that are owned. Some areas in Bali have their own uniqueness with the content of local culture such as handicraft sculpture from Uang Kepeng. At first the statue of Uang Kepeng was devoted to various kinds of Hindu traditional ceremonies in Bali, but now it has been designated for commercial purposes, which is usually this statue was purchased to add luxury to the interior of the guest room, hotel / villa waiting room, or luxury restaurant. The problems faced by the two partners include: 1) Do not have a bookkeeping to calculate profit and loss, the cost of production and the recording of assets owned. 2) Do not have SOP, either related to raw materials (Uang Kepeng) or the flow in the production process. 3) The equipment which is owned by its economic age has expired so that it often suffers damage such as shaved machines, sitting drills, sensor machines, grinders, jigsaw machines, and chisels. 4) Difficulties to meet the demand for Uang Kepeng due to rare species of Kepeng. 5) The size of the showroom and production site is very narrow so it is difficult to arrange between the production site and the showroom. 6) Marketing is done only with a blog and never updated information from